Stages Of Implementation Of Pedagogical Conditions For The Development Of Reflexive Competency Of Teachers Of The Future Primary Class - Khayitov A.I. (Periodica Journal, 2026)
This article describes the stages of implementing pedagogical conditions aimed at developing the reflexive competence of future primary school teachers.
Keywords: future teacher; primary education; reflexive competence